Does hybridization with a widespread congener threaten the long-term persistence of the Eastern Alpine rare local endemic Knautia carinthiaca? - Čertner, Martin; Kolář, Filip; Schönswetter, Peter; Frajman, Božo (Ecology and evolution, 2015)
Interspecific hybridization, especially when regularly followed by backcrossing (i.e., introgressive hybridization), conveys a substantial risk for many endangered organisms. This is particularly true for narrow endemics occurring within distributional ranges of widespread congeners. An excellent example is provided by the plant genus Knautia (Caprifoliaceae): Locally endemic K. carinthiaca is reported from two isolated populations in southern Austria situated within an area predominantly occupied by widespread K. arvensis. While K. carinthiaca usually inhabits low-competition communities on rocky outcrops, K. arvensis occurs mainly in dry to mesic managed grasslands, yet both species can coexist in marginal environments and were suspected to hybridize. Flow cytometry revealed that diploid K. carinthiaca only occurs at its locus classicus, whereas the second locality is inhabited by the morphologically similar but tetraploid K. norica. In the, therefore, single population of K. carinthiaca, flow cytometry and AFLP fingerprinting showed signs of introgressive hybridization with diploid K. arvensis. Hybridization patterns were also reflected in intermediate habitat preferences and morphology of the hybrids. Environmental barriers to gene flow seem to prevent genetic erosion of K. carinthiaca individuals from the core ecological niches, restricting most introgressed individuals to peripheral habitats. Efficient conservation of K. carinthiaca will require strict protection of its habitat and ban on forest clear cuts in a buffer zone to prevent invasion of K. arvensis. We demonstrate the large potential of multidisciplinary approaches combining molecular, cytometric, and ecological tools for a reliable inventory and threat assessment of rare species.
Keywords: relict; human‐induced landscape changes; introgression; steno‐endemic species; Eastern Alps; habitat segregation